The Coronavirus Pandemic: Experience From a Rural West Virginia Tertiary Care Hospital. Issue 6 (June 2020) - Richmond, Bryan K.
The coronavirus epidemic has taken the world by storm and has overwhelmed health systems in a number of first world countries. As a consequence, individual communities in the United States and the world have had to develop response plans to meet this extreme challenge. In these circumstances and in an effort to best prepare for the community's needs, it becomes necessary to critically analyze the specific and unique aspects of individual regions, their population characteristics and demographics, and the geography of the area. Once assessed, these data may be applied to formulating best practices for a given community and resource pool. The following manuscript describes how this challenge was met in a large tertiary care teaching hospital located in rural West Virginia.